The happiness files : insights on work and life - Brooks, Arthur C., 1964- (Harvard Business Review Press, 2025)
Imagine if your life were a startup. How would you lead it and shape it to be most successful? That's the question behind The Happiness Files, a rich selection of enlightening and instructive essays by Arthur C. Brooks, known worldwide for his inspiring yet practical wisdom and advice in his weekly column for The Atlantic and in his bestselling books, From Strength to Strength and Build the Life You Want (coauthored with Oprah Winfrey). The simple answer, as Brooks wisely explains, is to manage your life in a way that leads to truly valuable rewards: love, enjoyment, satisfaction, and meaning--in other words, happiness. Building on his popular Harvard Business School course "Leadership and Happiness," Brooks begins each essay with sharp observations and behavioral science research that shed light on how happiness really works, then offers experiential wisdom and practical advice. Beautifully written, the essays range from ancient philosophy to literature, pop culture, and the contemporary world of work. They explore topics and challenges such as "Procrastinate This, Not That," "Why Success Can Feel So Bitter," and "Five Pillars of a Good Life." Readers will find the chapters helpfully grouped by theme: "On Managing Yourself," "On Jobs, Money, and Building Your Career," "On Balancing Work, Life, and Relationships," and more. We all need more happiness in our work and in our lives. In The Happiness Files you'll find enlightenment, inspiration, and useful guidance for leading a happier, more successful, and more fulfilling life and career. -- Provided by publisher.